Challenges of Hybridity in Transcultural Identity: A Case of Displaced Universities - Terepyshchyi, Serhii; Dunets, Vasyl; Dmytro, Kalach (Studia Warmińskie, 2018)
The system of higher education in Ukraine is regulated by the Law on Higher Education of 2002, it was amended in 2014 and this is still valid today. Within its framework, a new state policy in the sphere of education was defined, a new structure of higher education was developed and recommendations were made regarding the curricula and their implementation. A decision was also made to rebuild the network of higher education institutions and to make them new, and to give universities greater autonomy in many areas. The biggest problems with higher education are related to the situation in the Crimea and Donbas region, as many students and teachers can not continue to work and study at their home universities. Hence the decision was made to transfer the university to other cities. These are not short-term and easy projects. The authors, analyzing this problem, emphasize that the situation of transferred (evacuated) universities should always be considered from the perspective of two cities: the one from which the university was evacuated and the one to which it was transferred. Many people are involved in this process, but while in many cases it is possible to save the material resources of the university, it is more difficult to take care of an individual. The authors note that de facto, even under the most favorable circumstances, it is impossible to fully integrate the university after moving to a new place, even if it was previously a cohesive organism. However, in the current situation it is the only and right way to study and to keep jobs. The authors based their analyzes on a survey conducted in 2018 with students from six transferred universities. The problems mentioned by the authors concern in fact as many as 18 universities and several scientific institutions, i.e. about three and a half thousand academic and pedagogical employees, and almost forty thousand students.